The Use Of “Movie Watch” Activities In Improving Students’ English Speaking Ability In the Front of Class - Mufida; Prayitno, Harun Joko; Wicaksono, Bayu Hendro (Jurnal Ilmiah Kampus Mengajar, 2024)
English language skills are very necessary to face the era of society 5.0. Currently, Indonesia is ranked 81st out of 111 countries in the world, so there is an urgency to improve students' English-speaking skills. The aim of this research is to improve students' English-speaking skills through watching movies. This research activity involved 24 third-grade students at Pajang III State Elementary School Laweyan. This research was carried out for one month, from October 10 to November 7, 2023. The research method was classroom action research (CAR), with a qualitative and quantitative approach. The data analysis technique used in this research uses the Miles and Huberman model, which consists of: 1) data collection; 2) data reduction; 3) pre-presentation or display of data; and 4) drawing conclusions. The result of this research shows that students English speaking skills improved in every aspect from the pretest to posttest stages through the use of movie watching activities. The implementation of this research was carried out by asking students to read one sentence of dialogue in the movie, then the researcher would show the movie so that students knew the correct way to pronounce it. By utilizing movie watching activities, it can stimulate students ability to pronounce words more crearly and with this activity students have new experiences in learning english at school.